2002
DOI: 10.1007/s00228-002-0491-0
|View full text |Cite
|
Sign up to set email alerts
|

Ibuprofen arginate provides effective relief from postoperative dental pain with a more rapid onset of action than ibuprofen

Abstract: Ibuprofen is a safe and effective analgesic, but some formulations have a slow onset of action. Ibuprofen arginate is a rapidly absorbed salt designed to promote more rapid onset of analgesia. A clinical trial was conducted in 226 patients with postoperative dental pain to assess the analgesic efficacy and speed of onset of the arginine salt of ibuprofen compared with one of the commercially available forms of ibuprofen. Patients were administered a single dose of either ibuprofen arginate (200 mg or 400 mg), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
54
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(56 citation statements)
references
References 12 publications
2
54
0
Order By: Relevance
“…[15][16][17] This clinical trial supports the hypothesis that ibuprofen arginate is as efficacious as conventional ibuprofen, but with a faster onset of action. In this study, ibuprofen arginate was shown to have significantly faster pain relief than conventional ibuprofen.…”
Section: Discussionsupporting
confidence: 69%
“…[15][16][17] This clinical trial supports the hypothesis that ibuprofen arginate is as efficacious as conventional ibuprofen, but with a faster onset of action. In this study, ibuprofen arginate was shown to have significantly faster pain relief than conventional ibuprofen.…”
Section: Discussionsupporting
confidence: 69%
“…For the primary endpoint, data were available for the time to perceptible relief from three studies using ibuprofen arginate [11,12,19]. These data suggested that the time to perceptible relief would be 9 to 14 min for the two test formulations, assuming a similar onset of action to that of ibuprofen arginate.…”
Section: Sample Size Determinationmentioning
confidence: 99%
“…The formulation used in this study contains 256 mg of the ibuprofen sodium salt, equivalent to 200 mg ibuprofen acid. It is well documented that ibuprofen salts, such as ibuprofen sodium, lysine and arginate, are more rapidly absorbed than formulations of free ibuprofen acid [9], and several studies have shown that faster absorbed formulations lead to faster onset of analgesia [10][11][12]. The salt dissolves rapidly in the gastrointestinal tract, leading to faster absorption.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations